Konsep Dasar Semiotika dalam Komunikasi Massa menurut Charles Sanders Pierce - Dadan Suherdiana (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
Sign or symbol in mass communication is not something with without makna. Nevertheless, it is not easy for anyone to can comprehend that sign. Minimally, that is a method for it, is named semiotic. Charles Sanders Pierce introduce pragmatism for this method. For him, semiotics have three researches area: syntactic semiotic, semantic semiotic and pragmatic semiotic. Sintaktic semiotic, teach the relation between sign with others sign; semantic semiotic, teach the relation and consequence in interpretant/ relation between sign and its denotation; pragmatic semiotic, teach relation between sign with user of sign.